PENGUKURAN TINGKAT EFEKTIVITAS MESIN MILLING DI PT NOK FREUDENBERG BATAM - Lumbantoruan, Imran Suriadi; susanti, Elva (LPPM Universitas Putera Batam, 2021)
The CNC Milling Makino V33 is a machine used for the manufacture of protrusions and holes. When carrying out the production process, this machine often experiences problems such as overheating on the Y and X axes, misuse of materials and others that cause unattainable output. This study aims to measure the level of machine effectiveness using Overall Equipment Effectiveness (OEE), identify six big losses with Pareto diagrams, fishbone diagrams and Failure Mode Analysis (FMEA) and provide suggestions for engine improvements. Based on the research results, the OEE of the CNC Milling Makino V33 machine for the January 2020-August 2020 period was 29.37% and was still below the OEE International standard value of 85%. Based on calculation of the RPN value that has been carried out, the highest cause of failure is the unstable heater temperature. Proposed improvements that can be done are to check the heater temperature and carry out preventive maintenance every month.